Private Police and Security Governance: Mapping Emerging Trends and Future Directions - Nalla, Mahesh (Journal of contemporary criminal justice, 2020)
In this article, we outline a brief overview of the growth and trends in scholarly literature devoted to the study of private policing and the private security industry in crime and security governance over the past five decades. More specifically, we draw attention to the scholarship addressing private policing and the shifts in the discourse of the subject of security governance during this time both from theoretical and thematic foci. In doing so, we identify potential future directions in which this field of private policing studies is moving.